Axisymmetric Elastoplastic State of Compound Shells Subject to Thermal and Mechanical Loading and Radiation Exposure - Babeshko, M. E.; Savchenko, V. G. (International applied mechanics, 2017)
A method for numerical analysis of the thermal elastoplastic axisymmetric stress–strain state of thin layered shells made of isotropic and transversely isotropic materials subject to thermal and mechanical loading and radiation exposure is proposed. The constitutive equations of isotropic thermoplasticity and transversely isotropic elasticity are used. The elastoplastic state of a two-layer plate subject to radiation exposure is determined and analyzed.